2007
DOI: 10.1196/annals.1392.000
|View full text |Cite
|
Sign up to set email alerts
|

Novel Markers for the Prospective Isolation of Human MSC

Abstract: The isolation of mesenchymal stem cells (MSC) from primary tissue is hampered by the limited selectivity of available markers. So far, CD271 is one of the most specific markers for bone marrow (BM)-derived MSC. In search of additional markers, monoclonal antibodies (mAbs) with specificity for immature cells were screened by flow cytometry for their specific reactivity with the rare CD271(+) population. The recognized CD271(+) populations were fractionated by fluorescence-activated cell sorting and the clonogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
302
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(323 citation statements)
references
References 19 publications
10
302
2
4
Order By: Relevance
“…In our study, bone precursor cells from bone marrow aspirates of orthopedic patients were used to analyze bone stem cell behavior when cultured in close contact with selected scaffolds. The cell population was previously analyzed for the presence of specific surface antigens/biomarkers, as reported in earlier studies [16]. In our investigation, hMSCs maintained their self-renewal capacity during 5 culture passages by increasing the cumulative number of cell doublings.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In our study, bone precursor cells from bone marrow aspirates of orthopedic patients were used to analyze bone stem cell behavior when cultured in close contact with selected scaffolds. The cell population was previously analyzed for the presence of specific surface antigens/biomarkers, as reported in earlier studies [16]. In our investigation, hMSCs maintained their self-renewal capacity during 5 culture passages by increasing the cumulative number of cell doublings.…”
Section: Discussionmentioning
confidence: 67%
“…The negative selection of hMSC was performed with the following markers: FITC anti-human CD45 (Bioscience, clone IgG1 HI30), PE anti-human CD235a (glycophorin A, Bioscience clone IgG2b HIR2). hMSCs were analyzed using FCA (Becton-Dickinson, Milan, Italy) after PBS washes [16].…”
Section: Flow Cytometric Analysis (Fca) Of Hmscsmentioning
confidence: 99%
“…LNGFR is not reactive to red blood cells and hematopoietic progenitor cells, which has made LNGFR one of the more popular markers for the isolation of human MSCs. Some studies have used the LNGFR marker in combination with MSCA-1-positive [51], CD56-positive [52,53], CD140b-positive [54], CD146-positive/negative [55], and SSEA4-positive [56] populations. In addition, high CFU-F frequency is associated with a population double-positive for CD106 (VCAM-1) and Stro-1 antibodies [57].…”
Section: Prospective Identification and Isolation Of Human Mscsmentioning
confidence: 99%
“…Surface markers such as stage-specific embryonic Ag-4, STRO-1 and the low-affinity nerve growth factor receptor (CD271) have been employed with the aim to prospectively isolate human MSCs. [9][10][11] Battula et al 12 have recently identified novel MSC subsets with distinct phenotypic and functional properties in human BM by using antibodies directed against the surface Ags CD271, mesenchymal stem cell Ag-1 and CD56. In particular, CD271 has been reported to define a subset of MSCs with immunosuppressive and lymphohematopoietic engraftment-promoting properties in vivo.…”
Section: Msc Surface Markersmentioning
confidence: 99%
“…6,7 Recently, the identification and prospective isolation of mesenchymal progenitors, both in murine and human adult BM, have been reported, based on the expression of specific markers. [8][9][10][11][12][13][14] Whether culture-expanded MSCs differ from their progenitors in vivo is uncertain, as proliferation on plastic surfaces and culture conditions may induce both phenotypic and functional changes. Anjos-Afonso et al 8 have reported the identification, isolation and characterization of a population of multipotent mesenchymal cells in murine BM, based on the expression of the stage-specific embryonic antigen-1.…”
Section: Msc Surface Markersmentioning
confidence: 99%